IMPLEMENTATION OF ELECTRONIC TICKET SANCTIONS FOR TRAFFIC VIOLATORS IN BONE DISTRICT - Safina Safina; Muhammad Lutfi; Muhammad Takdir (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
The transportation system is very important in a city, both in big cities and small cities. There are so many traffic violations that occur on the highway caused by road users who do not obey traffic rules, this can cause congestion and can even cause traffic accidents. With the E-Tilang service, the implementation of traffic tickets is faster than manual tickets, besides that there is transparency or openness in its implementation. The method used in this research uses a qualitative research method with a literature study approach to explain the application of e-Tilang sanctions in Bone Regency. The application of e-Tilang sanctions in Bone Regency has not been implemented optimally because the socialization carried out by law enforcement officials has not been maximized so that there are still people who do not know about the implementation of e-Tilang and the community still does not fully support e-Tilang because of the high costs that must be incurred.